Analisis Faktor Yang Mempengaruhi Perilaku Keluarga Dalam Upaya Pencegahan ISPA Pada Balita Di Puskesmas Marina Permai Palangka Raya - Hermanto Hermanto; Agustina Nugrahini; Febrianto Eka Putra (Pusat Riset dan Inovasi Nasional, 2023)
Toddlers are children aged 0-59 months during this growth period, the organs in the body of toddlers are undergoing development, including their immune system. One of the main reasons they are susceptible to Upper Respiratory Tract Infections is because their immune system is not yet fully formed. Family behavior is an important element in efforts to prevent diseases in children, including the prevention of Upper Respiratory Tract Infections or reducing morbidity, mortality rates of toddlers. This study aims to determine the influence and relationship between knowledge, family attitudes, health worker behavior and utilization of health facilities with family behavior at Marina Permai Palangka Raya Health Center. This type of research is Associative using Cross Sectional approach with Statistical Test of Multiple Linear Regression Analysis. Sampling technique with Purposive Sampling the sample size was 43 Respondents. The results showed that there was no relationship between knowledge and family behavior with a p velue of 1.533, no relationship between family attitudes and family behavior with a p velue of 0.321, no relationship between health worker behavior and family behavior with a p velue of 0.150, no relationship between utilization of health facilities and family behavior with a p velue of 1.152. Based on the simultaneous test with the results of 0.955, it means that there is no relationship between knowledge factors, family attitudes, health worker behavior and utilization of health facilities. The conclusion of this study is that family behavior is influenced by other factors and there is no influence between knowledge factors, family attitudes, health worker behavior and facility utilization.